The Role of Religious Scholars in Preventing the High Incidence of Alcohol Consumption Among Teenagers - Ainul Kamalia; Abdulloh (Journal of Practice Learning and Educational Development, 2025)
The rising phenomenon of alcohol consumption among rural adolescents poses a serious challenge with wide-ranging impacts on the social, moral, and health aspects of society. This study aims to describe the role of religious scholars (ulama) in preventing alcohol abuse among teenagers in Sumberagung Village, Sumbermanjing Wetan District. This research employs a qualitative approach with a case study method, in which data were obtained through in-depth interviews with five local ulama. The findings indicate that ulama play a strategic role through various religious activities, such as regular Quranic study groups at the neighborhood level (RT/RW), Friday sermons, the establishment of majelis taklim (religious gatherings focused on selawat), and youth empowerment through martial arts training. These efforts have positively influenced the character development and religious awareness of adolescents, although challenges remain, such as environmental factors, family dynamics, and weak supervision of alcohol distribution. This study recommends strengthening collaboration between ulama, families, village governments, and educational institutions to create a supportive environment for the healthy and religious growth of youth.